2020
DOI: 10.1371/journal.pone.0236706
|View full text |Cite
|
Sign up to set email alerts
|

Differing interpretations of health care encounters: A qualitative study of non-Latinx health care providers’ perceptions of Latinx patient behaviors

Abstract: Introduction Due to provider shortages, it is probable that non-Latinx health care providers (HCPs) will treat Latinx patients. Because of this discrepancy, both providers and patients are likely to experience barriers and cultural differences during medical encounters. This article discusses select cultural factors and behaviors such as language, communication styles, and health care practices of Latinx families through the lens of their non-Latinx HCPs. The purpose of this study was to examine how non-Latinx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Over half of the caregivers who described their ethnicity as Hispanic/Latino in this study reported feeling that they received lower quality care compared to their non-Hispanic/Latino counterparts, due to communication barriers and PCPs failing to provide culturally responsive care. Caregiver participants reported that quality of care might also be diminished "partly also because we say nothing, " which is consistent with previous literature suggesting that the experience of common Latino cultural tenets of respeto and confianza can influence families to be "grateful and not complain, " even if they are seemingly subjected to inadequate care (56). According to the 2020 census, Hispanic/Latino individuals account for 18.7% of the United States population (57), so it is essential to reduce the immense health disparities faced by Hispanic/Latino autistic adults whose health inequities are shaped by the cumulative effects of belonging to two marginalized groups.…”
Section: Discussionsupporting
confidence: 86%
“…Over half of the caregivers who described their ethnicity as Hispanic/Latino in this study reported feeling that they received lower quality care compared to their non-Hispanic/Latino counterparts, due to communication barriers and PCPs failing to provide culturally responsive care. Caregiver participants reported that quality of care might also be diminished "partly also because we say nothing, " which is consistent with previous literature suggesting that the experience of common Latino cultural tenets of respeto and confianza can influence families to be "grateful and not complain, " even if they are seemingly subjected to inadequate care (56). According to the 2020 census, Hispanic/Latino individuals account for 18.7% of the United States population (57), so it is essential to reduce the immense health disparities faced by Hispanic/Latino autistic adults whose health inequities are shaped by the cumulative effects of belonging to two marginalized groups.…”
Section: Discussionsupporting
confidence: 86%
“…This preference was more robust for older participants who identified potential barriers, and text messaging's impersonal nature as an issue (Soto et al, 2018). These concerns are also in line with the cultural values of Simpatia (kindness) and Personalismo (relationships), which are essential aspects of care in Latinx populations (Floríndez et al, 2020;Knight & Sayegh, 2010). The warm, friendly, and personalized interactions that are core facets of Personalismo and Simpatia may be missing in text messaging, especially if the messages are not personalized to recipients.…”
Section: Discussionmentioning
confidence: 63%
“…This finding held true across all education levels, income levels, country of origin, and regardless of ASD diagnosis, suggesting that this sacrifice made by parents for promoting the health of their children that is broadly shared within Latinx families. While observed in Latinx parents in other care settings, 39 more testing would have to be done to draw conclusions as to whether this finding is exclusive to Latinx parents, this finding has larger implications about the impact of familismo, the Latinx cultural value of placing family first, 26 and how the Latinx parents surveyed supported this concept.…”
Section: Discussionmentioning
confidence: 93%